2002
DOI: 10.1016/s0044-8486(02)00064-9
|View full text |Cite
|
Sign up to set email alerts
|

Increased activities of hepatic antioxidant defence enzymes in juvenile gilthead sea bream (Sparus aurata L.) fed dietary oxidised oil: attenuation by dietary vitamin E

Abstract: Previously, we had shown that altering the highly unsaturated fatty acid(HUFA)/vitamin E ratios in sea bream (Sparus aurata) livers significantly affected their peroxidation status, with fish fed the diet rich in HUFA and low in vitamin E showing significantly higher values of lipid peroxidation products, without, however, significant effects on liver antioxidant defence enzyme activities. The aim of the present trial was to further characterise the biochemical indicators of peroxidative stress in juvenile sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
132
3
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 229 publications
(159 citation statements)
references
References 49 publications
(44 reference statements)
22
132
3
2
Order By: Relevance
“…Moreover, by metabolizing lipid hydroperoxides in response to ROS production, GST plays a critical role in the antioxidant defense system [32]. In this study, the marked increase of GST activity was observed in the fi sh liver exposed to Fl and Fluo alone.…”
Section: Discussion Of Resultssupporting
confidence: 49%
“…Moreover, by metabolizing lipid hydroperoxides in response to ROS production, GST plays a critical role in the antioxidant defense system [32]. In this study, the marked increase of GST activity was observed in the fi sh liver exposed to Fl and Fluo alone.…”
Section: Discussion Of Resultssupporting
confidence: 49%
“…However, feeding high HUFA diets resulted in signs of increased peroxidative stress in juvenile marine fish, as evidenced by increased levels of tissue lipid peroxidation products, and some moderate effects on liver antioxidant defence enzyme activities were observed (Tocher et al, 2002a). In a very recent study using diets containing very high levels of n-3 HUFA and pre-oxidised oil, the activity of the enzyme defence system was clearly demonstrated to be increased by feeding oxidised oil and reduced by supplementing the diets with vitamin E in sea bream (Mourente et al 2002). In a related comparative study, the liver antioxidant defence enzymes did not respond to dietary oxidised oil or vitamin E in halibut as occurred in sea bream and turbot suggesting that there may be species differences in this defence system perhaps related to temperature or developmental stage (Tocher et al, 2002b).…”
Section: Functionsmentioning
confidence: 99%
“…Antioxidant enzymes constitute one of the major cellular protective mechanisms against oxidative stress in fish (Mourente et al, 2002). Activities of antioxidant enzymes are related to their mRNA expression in fish tissue .…”
Section: Introductionmentioning
confidence: 99%